Plan de marketing para el posicionamiento en el mercado del almacén de telas multicolor GYGY, de la ciudad de Guaranda, provincia Bolívar, período 2023-2027. - Aguay Cuestas, Christian Patricio (2024)
This marketing plan called “Market Positioning” focused on the possibility of how to position the name “GYGY warehouses”, identifying customer demands, knowing the style in which the market develops competitive activities. The proposal of this marketing plan is to position the brand, applying strategies that support customers that the qualities and virtues are the best strengths compared to the competencies, the Store will focus on implementing exclusivity, seriousness, service, communication and An excellent ability to provide credibility to the client will be guaranteed as an institutional policy, obtaining the best seriousness of the case towards clients who demand quality attention. To understand the current needs of customer demands, appropriate market research is carried out and the results are presented to obtain more accessible knowledge of the market and the best strategies that should be implemented for the benefit of Store GYGY.